2002
DOI: 10.1177/147323000203000208
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Comparison of Psoas Compartment and Inguinal Paravascular Blocks Combined with Sciatic Nerve Block

Abstract: The extent of inguinal paravascular blockade and psoas compartment blockade with sciatic nerve block was evaluated in 60 patients. Volumes of 30 ml and 20 ml 0.35% bupivacaine with 1/200,000 epinephrine were injected for lumbar plexus and sciatic nerve block, respectively. Complete lumbar plexus blockade was achieved in 73% of the group who were treated with the psoas compartment technique and 43% of the group who were treated with the inguinal paravascular technique. Sensory blockade of the femoral, lateral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 11 publications
4
24
2
1
Order By: Relevance
“…7,10,12 Two RCTs have reported a higher success rate for blockade of the lateral femoral cutaneous nerve with the posterior approach (90-97 vs 50-53%; P < 0.05) 10,12 whereas another study found no difference (85-95%). 7 All four RCTs reported significantly better obturator block with the posterior approach: three RCTs noted an improved sensory block (77-80 vs 47-50%; P < 0.05) [10][11][12] while two studies also found a higher rate of motor block (63-100 vs 0-30%; P < 0.05). 7,10 However, in 45 patients undergoing total hip replacement, one study compared single shot lumbar plexus and 3-in-1 blocks and failed to detect any difference in nerve block distribution.…”
Section: Approachesmentioning
confidence: 92%
See 1 more Smart Citation
“…7,10,12 Two RCTs have reported a higher success rate for blockade of the lateral femoral cutaneous nerve with the posterior approach (90-97 vs 50-53%; P < 0.05) 10,12 whereas another study found no difference (85-95%). 7 All four RCTs reported significantly better obturator block with the posterior approach: three RCTs noted an improved sensory block (77-80 vs 47-50%; P < 0.05) [10][11][12] while two studies also found a higher rate of motor block (63-100 vs 0-30%; P < 0.05). 7,10 However, in 45 patients undergoing total hip replacement, one study compared single shot lumbar plexus and 3-in-1 blocks and failed to detect any difference in nerve block distribution.…”
Section: Approachesmentioning
confidence: 92%
“…7 All four RCTs reported significantly better obturator block with the posterior approach: three RCTs noted an improved sensory block (77-80 vs 47-50%; P < 0.05) [10][11][12] while two studies also found a higher rate of motor block (63-100 vs 0-30%; P < 0.05). 7,10 However, in 45 patients undergoing total hip replacement, one study compared single shot lumbar plexus and 3-in-1 blocks and failed to detect any difference in nerve block distribution. 13 Two RCTs (combined n = 119) have compared continuous posterior and anterior approaches for patients undergoing total knee replacement.…”
Section: Approachesmentioning
confidence: 99%
“…Le suivi des patients à distance n'a montré aucune complication clinique neurologique locale à type de paresthésie, dysesthésie ou faiblesse musculaire. D Di is sc cu us ss si io on n Si de nombreux auteurs ont étudié le taux d'échec des blocs périphériques et en particulier du bloc fémoral selon différentes techniques de ponction, [14][15][16] seulement deux études se sont intéressées au taux d'échec sur le nerf saphène lors de la réalisation d'un bloc fémoral, que ce soit avec recherche de paresthésie ou à l'aide d'un neurostimulateur avec respectivement 23 % et 16 % d'échec. 3,11 Le taux d'échec global de 20 % de notre étude confirme les résultats de Bouaziz et coll.…”
Section: Methodsunclassified
“…Some investigators have questioned its efficacy due to incomplete block of obturator nerve. 1,2 Failure to achieve block of this nerve may cause incomplete analgesia after hip surgery. better analgesia after hip operation.…”
Section: Inguinal Perivascular Technique (Anterior Approach) or (Ii) mentioning
confidence: 99%
“…better analgesia after hip operation. 2 The present study was done to compare the efficacy of "3 in 1"block versus psoas compartmental block in relieving post-operative pain for orthopedic procedures in hip, femur and knee surgeries.…”
Section: Inguinal Perivascular Technique (Anterior Approach) or (Ii) mentioning
confidence: 99%